2023
DOI: 10.1177/07340168231190673
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19, Diffuse Anxiety, and Public (Mis)Trust in Government: Empirical Insights and Implications for Crime and Justice

Abstract: Given that trust in government is a critical feature of a well-functioning democracy, research into its determinants has long been a priority among public opinion scholars. The consensus in the literature is that short-term factors drive the ebbs and flows of public trust, and a climate of mistrust has significant consequences on the government's ability to deliver on policies and enforce the law. Despite decades of extensive research on public trust, changing circumstances related to the COVID-19 pandemic sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Women’s health, including access to reproductive and maternal healthcare services and increased susceptibility to infectious diseases, could be adversely impacted as a result. Studies have found that mistrust of the government affected the adoption of COVID-19 protocols, increasing its prevalence rate [ 72 , 73 , 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Women’s health, including access to reproductive and maternal healthcare services and increased susceptibility to infectious diseases, could be adversely impacted as a result. Studies have found that mistrust of the government affected the adoption of COVID-19 protocols, increasing its prevalence rate [ 72 , 73 , 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of the current study and prior research collectively point to the need for future research to examine potential intergroup conflicts and competition outside the White-Black dichotomy, such as between African Americans and Hispanics. This avenue of research is especially pertinent to the current context of race relations (Bobo, 2017) as the racial-ethnic demographics of the nation continue to shift and as Americans continue to navigate socioeconomic and political challenges brought on by the COVID-19 pandemic (see generally, Reid et al, 2023).…”
Section: Discussionmentioning
confidence: 99%